2014
DOI: 10.1007/s10646-014-1305-8
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the brain proteome of Africanized honeybees (Apis mellifera) exposed to a sub‐lethal doses of the insecticide fipronil

Abstract: Fipronil is a phenylpyrazole insecticide that is widely used in Brazilian agriculture for pest control. Although honeybees are not targets of fipronil, studies indicate that this pesticide can be harmful to honeybees. To assess the effects of fipronil in the brain of Africanized Apis mellifera workers, this study focused on the toxico-proteome profiling of the brain of newly emerged and aged honeybee workers that were exposed to a sub-lethal dose (10 pg fipronil per day. i.e. (1)/100 of LD50/bee/day during 5 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Gels from bees exposed to pesticides were individually subject to pairwise comparisons to the control group to deduce the fold expression level of proteins. For this, the relative volume parameter (%Vol) was used, which has been reported to be an efficient measure because it takes into account variation due to protein loading and staining by considering the total volume over all the spots in the gel [29][30][31] .…”
Section: Resultsmentioning
confidence: 99%
“…Gels from bees exposed to pesticides were individually subject to pairwise comparisons to the control group to deduce the fold expression level of proteins. For this, the relative volume parameter (%Vol) was used, which has been reported to be an efficient measure because it takes into account variation due to protein loading and staining by considering the total volume over all the spots in the gel [29][30][31] .…”
Section: Resultsmentioning
confidence: 99%
“…Roat et al (2014) found changes in the brain proteome of Africanized honeybees for doses of 10 pg fipronil per day during 5 days. Concentrations of several brain proteins involved in detoxification, glycolysis, and cell growth were altered, possibly leading to memory and learning impairment and to a reduced life span.…”
Section: Experimental (In Vitro) Studiesmentioning
confidence: 94%
“…Rosa et al (2016) found decreased larval survival feeding field-realistic doses (0.004 to 4.375 ng/larva) of thiamethoxam to Scaptotrigona depilis larvae in vitro. Low doses of fipronil (0.27 ng/bee topical, 0.24 ng/bee oral) affected brain morphology by apoptosis or necrosis of mushroom bodies of Scaptotrigona postica (Jacob et al 2015), comparable to its effect on mushroom bodies of A. mellifera (Roat et al 2014). Tomé et al (2012) also found effects of imidacloprid on mushroom bodies and behavior in Melipona quadrafasciata and showed that imidacloprid impaired respiration and flight activity in this species.…”
Section: Other Pollinatorsmentioning
confidence: 94%
“…Both proteomic approaches have been increasingly adopted for insect pest management research (Table ). The examples of applications include insect–plant host interactions (Dastranj, Gharechahi, & Salekdeh, ), characterizing mechanism of action of synthetic and bio‐based insecticides (Dong et al, ; Erban, Harant, Chalupnikova, Kocourek, & Stara, ; J. M. Park et al, ; Roat et al, ), assessing impact of insecticides of nontarget organisms (Vioque‐Fernández, De Almeida, & López‐Barea, ), and characterizing EPM in managing insect pests. Contemporary proteomics research has the options of adopting gel‐based or MS‐based, labeled or nonlabelled approach to answer biological questions (Figure ).…”
Section: Proteomics and Its Potential For Characterizing Microbe–hostmentioning
confidence: 99%